A microRNA Cluster Controls Fat Cell Differentiation and Adipose Tissue Expansion By Regulating SNCG. Issue 4 (13th December 2021) - Rodríguez‐Barrueco, Ruth; Latorre, Jessica; Devis‐Jáuregui, Laura; Lluch, Aina; Bonifaci, Nuria; Llobet, Francisco J.; Olivan, Mireia; Coll‐Iglesias, Laura; Gassner, Katja; Davis, Meredith L.; Moreno‐Navarrete, José M.; Castells‐Nobau, Anna; et al.
Abstract: The H19X‐encoded miR‐424(322)/503 cluster regulates multiple cellular functions. Here, it is reported for the first time that it is also a critical linchpin of fat mass expansion. Deletion of this miRNA cluster in mice results in obesity, while increasing the pool of early adipocyte progenitors and hypertrophied adipocytes. Complementary loss and gain of function experiments and RNA sequencing demonstrate that miR‐424(322)/503 regulates a conserved genetic program involved in the differentiation and commitment of white adipocytes. Mechanistically, it is demonstrated that miR‐424(322)/503 targets γ ‐Synuclein (SNCG), a factor that mediates this program rearrangement by controlling metabolic functions in fat cells, allowing adipocyte differentiation and adipose tissue enlargement. Accordingly, diminished miR‐424(322) in mice and obese humans co‐segregate with increased SNCG in fat and peripheral blood as mutually exclusive features of obesity, being normalized upon weight loss. The data unveil a previously unknown regulatory mechanism of fat mass expansion tightly controlled by the miR‐424(322)/503 through SNCG. Abstract : Absence of H19X‐encoded miR‐424(322)/503 in mice results in altered progenitor/adipose stem cell homeostasis, adipose tissue expansion, and its expression is reduced in obese subjects. Mechanistically, epigenetically‐controlled miR‐424(322)/503 modulates adipocyte differentiation by regulating γ ‐Synuclein (SNCG). Expression levels of miR‐424(322)/503 and tissular/soluble SNCG co‐segregate with obesity in humans and can be modulated by weight loss surgically induced by gastric bypass.